Faktor-Faktor yang Mempengaruhi Perubahan Resistensi Vaskular Pulmonal segera Pasca Komisurotomi Mitral Transvena Perkutan pada Stenosis Mitral - Adi Purnawarman; Nur Haryono; Indriwanto Sakijan (Jurnal Kardiologi Indonesia, 2011)
Background. In mitral stenosis (MS) patients, the increase in pulmonary arterial pressure and severity of the clinical symptom is not always related to the severity mitral valve stenosis and mitral valve gradient, but the pulmonary vascular resistance (PVR) as well. Methods. It’s a cross sectional study. PVR is measurement with invasive procedure before and immediately after the Balloon Mitral Valvotomy (BMV) procedure. The analysis was performed to assess the correlation of the age, gender, mitral valve area (MVA), mitral valve gradient (MVG), systolic pulmonary artery preasure (sPAP), mean pulmonary artery preasure (mPAP), mean left atrial preasure (mLAP), mitral score and improvement of the PVR immediately after BMV procedure.Results. There were 136 patients with mitral stenosis in the period 2008 Jan – 2010 Oct. Seventy five subjects (55.1%) had a atrial fibrilation (AF), 4 subjects (2.9%) complicated with severe aortic stenosis and 2 (1.4%) moderate to severe mitral regurgitation. Of 29 subjects eligible, 65.5% were women with age of 34 (19-53) years. After BMV, MVA increase from 0.5 (0.2 -1.3) to 1.0 (0.3 to 2.4) cm2 (p <0.001), MVG decreased from 19.0 (4 -29) to 7,0 (2 -10) mmHg (p <0.001), cardiac output increased from 2.8 (1.7 to 4.6) to 3.2 (2 -6) L (p <0.001), mPAP decreased from 56.1 ± 12,1 to 41.4 ± 9.8 mmHg (p <0.001), sPAP decreased from 87 (28-110) to 69 (18-110) mmHg (p <0.001), mLAP decreased 28.9 ± 8.0 to 16.0 ± 6.8 mmHg (p <0.001) and PVR decreased from 9.0 (6.3 to 17.8) to 7.8 (2.6 to 14.3) (P <0.001) immediately after the procedure. MVA pre procedure was significant different between subject with and without PVR reduction below 6WU (0.6[0.4-1.3] vs 0.4[0.2-0.7], p=0.024). Logistic regression analysis showed MVA was a predictor of PVR reduction immediately after procedure (OR 0,003 with p value 0,04 and 95% C.I. 0,0001 – 0,766).Conclusion. The pre-procedure MVA is a predictor of PVR reduction immediately after BMV procedure.